REAÃ‡ÃƒO DE GENÃ“TIPOS DE SOJA A ð˜ð˜¦ð˜µð˜¦ð˜³ð˜°ð˜¥ð˜¦ð˜³ð˜¢ ð˜¨ð˜ð˜ºð˜¤ð˜ªð˜¯ð˜¦ð˜´ RAÃ‡A 3 EM CAMPO - Miranda, Manoel Albino Coelho de; Rossi, Carlos Eduardo; AraÃºjo, Ana Cristina MagalhÃ£es; Adde, Martim Francisco Villac (REVISTA DE AGRICULTURA, 2020)
REAÃ‡ÃƒO DE GENÃ“TIPOS DE SOJA A ð˜ð˜¦ð˜µð˜¦ð˜³ð˜°ð˜¥ð˜¦ð˜³ð˜¢ ð˜¨ð˜ð˜ºð˜¤ð˜ªð˜¯ð˜¦ð˜´ RAÃ‡A 3 EM CAMPO